2005
DOI: 10.5194/angeo-23-1711-2005
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the diurnal evolution of Ionospheric Alfvén resonator magnetic resonance features and calculation of changing IAR parameters

Abstract: Abstract. Resonance features of the Ionospheric AlfvénResonator (IAR) can be observed in pulsation magnetometer data from Sodankylä, Finland using dynamic spectra visualizations. IAR resonance features were identified on 13 of 30 days in October 1998, with resonance structures lasting for 3 or more hours over 10 intervals. The diurnal evolution of the harmonic features was quantified for these 10 intervals using a manual cursor-clicking technique. The resonance features displayed strong linear relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 13 publications
(25 reference statements)
7
73
0
2
Order By: Relevance
“…But sometimes the WKB approach gives satisfactory results for wavelengths comparable with the system size. In case of the IAR emission, we have long wavelengths for low harmonics, but the space between the harmonics is almost constant for all harmonics, as one can see from Figure 2 (see also Hebden et al 2005). This is a sign indicating that in this particular case the WKB can be applied, at least as a zero approximation.…”
Section: Calculations Based On the Standard Iri-2012 Modelmentioning
confidence: 62%
See 2 more Smart Citations
“…But sometimes the WKB approach gives satisfactory results for wavelengths comparable with the system size. In case of the IAR emission, we have long wavelengths for low harmonics, but the space between the harmonics is almost constant for all harmonics, as one can see from Figure 2 (see also Hebden et al 2005). This is a sign indicating that in this particular case the WKB can be applied, at least as a zero approximation.…”
Section: Calculations Based On the Standard Iri-2012 Modelmentioning
confidence: 62%
“…The frequency scale Df values were measured on spectrograms by using a manual on-screen cursor clicking technique for each pair of the adjacent bands opposite every hour mark given that the spectral bands (harmonics) of IAR emission were evident for that hour. (A similar technique was used in Hebden et al 2005.) Then, the Df values measured between different harmonic pairs were averaged providing one Df value for each hour.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Hebden et al (2005) observed harmonics up to almost 5 Hz from magnetometer data obtained from Sodankylä, Finland. These observations can be modeled using the equations in a tilted magnetic field geometry such as those introduced by Sciffer and Waters (2002).…”
Section: Effects Of Hall Conductance On the Iarmentioning
confidence: 99%
“…Bösinger et al, 2002;Semenova and Yahnin, 2008), usage in ionospheric diagnostics (e.g. Hebden et al, 2005;Odzimek et al, 2006), IAR's role in atmospheric, ionospheric, magnetospheric coupling (e.g. Lysak, 1993;Demekhov et al, 2000;Bösinger and Shalimov, 2008), non-linear effects (e.g.…”
Section: Introductionmentioning
confidence: 99%